Pemberdayaan Masyarakat dalam Peningkatan Kualitas Hidup melalui Literasi Keuangan Sejak Dini dan Pembuatan Sabun Cuci Piring di Desa Borong Pa’la’la - Daud, Dahniyar; Nur Uswatun Chasana; Mu’jizat; Nur Pausi; Andi Ashari; Naila Sasmita; Elina Sari Raimundus; Abdullah Al Ikhlas; Hendri Taufik; Ilham; Asrul Hasan (LOSARI DIGITAL, 2025)
The Field Work Program (KKL) Batch 51, Post 2, was conducted in Borong Pa’la’la Village, Patallassang District, Gowa Regency from July 24 to August 25, 2025, involving 10 students. The main issues addressed were limited financial literacy, low environmental awareness, and the need for women’s economic empowerment. The objective was to improve knowledge, independence, and community welfare. The program applied a participatory approach by engaging local residents in every activity. Strategies included early financial literacy education, the creation of waste bins, training in soap production for women’s groups (PKK), participation in the Independence Day celebration, and additional “Clean Saturday” activities. The outcomes showed improved community understanding of financial management, enhanced awareness of environmental hygiene, and increased skills among women in producing eco-friendly soap as a potential small business. Overall, the program contributed positively to capacity building and sustainable community development.